Influencing factors of sleep disorders and sleep quality in healthcare workers during the COVID‐19 pandemic: A systematic review and meta‐analysis - Qian Lv; Wenguang Zhou; Yue Kong; Silu Chen; Baoling Xu; Fangfang Zhu; Xianying Shen; Zhaojun Qiu (Nursing Open, 2023)
Abstract Aim The aim of this study was to identify the influencing factors of sleep disorders and sleep quality in healthcare workers during the COVID‐19 pandemic. Design Systematic review and meta‐analysis of observational research. Methods The databases of the Cochrane Library, Web of Science, PubMed, Embase, SinoMed database, CNKI, Wanfang Data, and VIP were systematically searched. The quality of studies was assessed using the Agency for Healthcare Research and Quality evaluation criteria and the Newcastle–Ottawa scale. Results A total of 29 studies were included, of which 20 were cross‐sectional studies, eight were cohort studies, and 1 was a case–control study; 17 influencing factors were finally identified. Greater risk of sleep disturbance was associated with female gender, single relationship status, chronic disease, insomnia history, less exercise, lack of social support, frontline work, days served in frontline work, department of service, night shift, years of work experience, anxiety, depression, stress, received psychological assistance, worried about being infected, and degree of fear with COVID‐19. Conclusions During the COVID‐19 pandemic, healthcare workers did have worse sleep quality than the general population. The influencing factors of sleep disorders and sleep quality in healthcare workers are multifaceted. Identification and timely intervention of resolvable influencing factors are particularly important for preventing sleep disorders and improving sleep. Patient or Public Contribution This is a meta‐analysis of previously published studies so there was no patient or public contribution.